Provider‐related barriers and enablers to the provision of hepatitis C treatment by general practitioners in Scotland: A behaviour change analysis. Issue 3 (7th December 2020) - Whiteley, David; Speakman, Elizabeth; Elliott, Lawrie; Davidson, Katherine; Hamilton, Emma; Jarvis, Helen; Quinn, Michael; Flowers, Paul
Abstract: The ease of direct‐acting antiviral (DAA) medications for hepatitis C virus (HCV) has provided an opportunity to decentralize HCV treatment into community settings. However, the role of non‐specialist clinicians in community‐based pathways has received scant attention to date. This study examined barriers and enablers to expanding the role of general practitioners (GPs) in HCV treatment provision, using simple behaviour change theory as a conceptual framework. A maximum variation sample of 22 HCV treatment providers, GPs and HCV support workers participated in semi‐structured interviews. Data were inductively coded, and the resulting codes deductively mapped into three principal components of behaviour change: capability, opportunity and motivation (COM‐B). By this process, a number of provider‐ and systemic‐level barriers and enablers were identified. Key barriers included the pre‐treatment assessment of liver fibrosis, GP capacity and the 'speciality' of HCV care. Enablers included the simplicity of the drugs, existing GP/patient relationships and the provision of holistic care. In addition to these specific factors, the data also exposed an overarching provider understanding of 'HCV treatment' as triumvirate in nature, incorporating the assessment of liver fibrosis, the provision of holistic support and the treatment of disease. This understanding imposes a further fundamental barrier to GP‐led treatment as each of these three components needs to be individually addressed. To enable sustainable models of HCV treatment provision by GPs, a pragmatic re‐examination of the 'HCV treatment triumvirate' is required, and a paradigm shift from the 'refer and treat' status quo.